A drive for structure: A longitudinal qualitative study of the implementation of the Carer Support Needs Assessment Tool (CSNAT) intervention during hospital discharge at end of life. (September 2020) - Hall, Alex; Ewing, Gail; Rowland, Christine; Grande, Gunn
Background: Informal carers are essential in enabling discharge home from hospital at end of life and supporting palliative patients at home, but are often ill-prepared for the role. Carers' support needs are rarely considered at discharge. If carers are less able to cope with home care, patient care may suffer and readmission may become more likely. Aim: To investigate the implementation of an evidence-based Carer Support Needs Assessment Tool (CSNAT) intervention to support carers during hospital discharge at end of life. Design: Longitudinal qualitative study with thematic analysis. Setting/participants: One National Health Service Trust in England: 12 hospital practitioners, one hospital administrator and four community practitioners. We provided training in CSNAT intervention use and implementation. Practitioners delivered the intervention for 6 months. Data collection was conducted in three phases: (1) pre-implementation interviews exploring understandings, anticipated benefits and challenges of the intervention; (2) observations of team meetings and review of intervention procedures and (3) follow-up interviews exploring experiences of working with the intervention. Results: Despite efforts from practitioners, implementation was challenging. Three main themes captured facilitators and barriers to implementation: (1) structure and focus within carer support; (2) the 'right' people to implement the intervention and (3) practical implementation challenges. Conclusions: Structure and focus may facilitate implementation, but the dominance of outcomes measurement and performance metrics in health systems may powerfully frame perceptions of the intervention and implementation decisions. There is uncertainty over who is best-placed or responsible for supporting carers around hospital discharge, and challenges in connecting with carers prior to discharge.